Hakekat Ilmu Pengetahuan Perspektif Islam Dan Barat: Tinjauan Ontologis - Dwi Ayu Nurfa’izah; Andini Pertiwi; Zuhdan Kun Prasetyo (Universitas Insan Budi Utomo, 2024)
Philosophy and science are two words that are interrelated, both historically and substantially. The scope of philosophy that questions about a reality in the universe, including science, is ontology. In the western and Islamic perspectives, ontology has given birth to several scientific studies. The purpose of this article is to examine the reality or nature of science from an ontological point of view, namely the essence of what it is, including the essence of knowledge itself as reality. Literature reviews are carried out on several relevant references, both from books and scientific articles related to the ontology of the nature of science. The results of the study of ontology of science include the breadth of science, the classification and hierarchy of science, the law of cause and effect, the nature of science, and various schools of ontological philosophy. The results of this study include a discussion of the nature of the physical nature, the concept of causal law, and the nature of science as a philosophical foundation for the development of sciences, especially in science. Overall, this study offers a comprehensive ontological perspective to understand and broaden insights into science and reality.